Pemanfaatan Limbah Cair untuk Bersuci yang Telah Diolah dalam Tinjauan Mazhab Syafi'i dan Mazhab Hanbali: The Utilization of Processed Liquid Waste for Purification in the Perspective of the Shafi'i and Hanbali Schools of Thought - Ariesman M; Saifullah Bin Anshor; Muammar Mahabuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to determine the opinion of the Syafi'ī school and the Hanbali school of using recycled liquid waste for purification. This study uses a type of library research, using a normative juridical approach. The results of this study indicate that the Syafi' and Hanbali schools have the same opinion, namely it is permissible to use treated liquid waste for purification, because in essence the end result of water treatment is to return polluted water to a good and safe condition for purification. so that the law of origin of the water becomes holy and purifying. Through the process of adding water (Mukaṡṡarah), or by allowing it to lose its change due to the length of time it has been left on, or removing the cause of the water changing / taking some of it.